2021
DOI: 10.3390/jmse9111158
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Shear Band of Methane Hydrate-Bearing Sediment

Abstract: The occurrence of a shear band is often thought as the precursor of failure. To study the initiation of shear banding in gas hydrate-bearing sediments, two groups of triaxial compression tests combined with a CT (computer tomography) scan were conducted by triaxial CT-integrated equipment under two confining pressures and seven hydrate saturations. The macro stress–strain curves and the corresponding CT scanning images of the micro-structure and the distribution of the components were obtained. The geometric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…This shows that with the increase in hydrate saturation, the stress−strain curve of sediments changes from strain hardening to strain softening. This is similar to the experimental results of sand sediments containing methane hydrate developed by Lu et al 40 They indicate that when the hydrate saturation exceeds 13%, the existence of methane hydrate changes the deformation failure of hydrate-bearing sediments from plastic failure to brittle failure. However, this is quite different from the failure modes of HBCS with high clay content (36%) and pure clay sediments.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This shows that with the increase in hydrate saturation, the stress−strain curve of sediments changes from strain hardening to strain softening. This is similar to the experimental results of sand sediments containing methane hydrate developed by Lu et al 40 They indicate that when the hydrate saturation exceeds 13%, the existence of methane hydrate changes the deformation failure of hydrate-bearing sediments from plastic failure to brittle failure. However, this is quite different from the failure modes of HBCS with high clay content (36%) and pure clay sediments.…”
Section: Resultssupporting
confidence: 91%
“…Hydrate Saturation Calculation Method. In this paper, the gas-excess method is used to generate hydrate, 40 and the hydrate saturation in sediments is indirectly estimated by controlling the water content in the sample. Assuming that all the water in the sample forms hydrate, the saturation of hydrate in the sediments can be converted according to the law of conservation of mass.…”
Section: Hydrate Saturation Calculation Methods and Test Conditionsmentioning
confidence: 99%
“…To investigate the shear band initiation within gas hydrate-bearing sediments, triaxial compression tests were conducted, combined with a computer tomography (CT) scan [17]. Their observations indicated that the shear band either occurred in a single oblique line or inter-cross lines depending on the hydrate saturation, the effective confining pressure and the initial distribution of the gas hydrate.…”
Section: (4) Properties Of Seabed Soils and The Materials For Deep-se...mentioning
confidence: 99%
“…1 Average abundance of pmoA genes calculated from the two treatments at each temperature. 2 One-way ANOVA was conducted with abundance of pmoA genes obtained from all six experimental treatments. 3 d.f is degree of freedom.…”
Section: Abundance Of Methanotrophic Populationmentioning
confidence: 99%
“…At present, gas hydrates are the most abundant source of methane on the earth [1][2][3]. A great amount of methane is released due to the decomposition of gas hydrates from submarine reservoirs [4], which are gradually consumed by anaerobic methanotrophic archaea (ANME) in anoxic sediment layers and aerobic methanotrophs in oxic layers [5,6].…”
Section: Introductionmentioning
confidence: 99%